Pathways to diverse diets - a retrospective analysis of a participatory nutrition-sensitive project in Kenya - Boedecker, Julia; Lachat, Carl; Hawwash, Damme; Damme, Patrick van; Nowicki, Marisa; Termote, Céline (Elsevier, 2021)
There is a current need for better understanding the impact of nutrition-sensitive agriculture interventions. This study is based on a community-based participatory project that diversified diets of women and children by making use of local food biodiversity. This retrospective impact pathway analysis aims at explaining why and how impact was reached. Pathway analysis in nutrition-sensitive agriculture can provide valuable understanding on how and why dietary improvements have been achieved in an intervention. The approach can hence be instrumental in addressing the current demand within the field on understanding the progress and impact of interventions. Pathway analysis also helps to address knowledge gaps regarding theoretical frameworks, as in the present study, concerning women empowerment pathways.